2006
DOI: 10.1017/s0022215106005585
|View full text |Cite
|
Sign up to set email alerts
|

Role of revision adenoidectomy in paediatric otolaryngological practice

Abstract: Adenoidectomy performed without vision may be one of the reasons for recurrence of symptoms. Residual adenoids are acknowledged in the literature as one of the complications of the traditional technique. We highlight the fact that the need for revision adenoidectomy is not uncommon and suggest that we should improve our surgical technique in the UK by visualization of the postnasal space either by a mirror or an endoscope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
3
17
0
Order By: Relevance
“…The incidence of re-growth is comparable to that shown by the retrospective analysis of conventional adenoidectomies, at approximately 1.6% [7].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The incidence of re-growth is comparable to that shown by the retrospective analysis of conventional adenoidectomies, at approximately 1.6% [7].…”
Section: Discussionsupporting
confidence: 64%
“…A recent retrospective study of over 3000 children undergoing adenoidectomy by blind curettage revealed a recurrence rate of 1.6% [7]. The authors suggest the use of a mirror or an endoscope to improve visualisation of the postnasal space.…”
Section: Introductionmentioning
confidence: 99%
“…This rate is in line with previously published re- ports. 1,2,4 The risk factors for repeated adenoidectomy identified in our initial cohort study include young age at the time of surgery and an adenoidectomy being performed without tonsillectomy. These findings are consistent with that of a few small studies that have suggested that a young age at the time of surgery increases the risk of having a repeated procedure.…”
Section: Commentmentioning
confidence: 99%
“…Previously published studies suggested that the rate of this phenomenon varied between 0% and 1.6%. 1,2 In a recent survey of otolaryngologists in the United Kingdom, 38.8% recognized that the need for revision adenoidectomy is a problem. 3 While it is a well-recognized entity, uncertainty remains regarding its risk factors.…”
mentioning
confidence: 99%
“…It decreases the frequency of pharyngitis for several years after surgery [6] and leads to a low incidence of tonsil regrowth [7]. The operation includes resection of the intact tonsil, its capsular and variable amounts of the surrounding mucosa and pillar muscle for surgical exposure.…”
Section: Discussionmentioning
confidence: 99%